2011
DOI: 10.1002/mc.20753
|View full text |Cite
|
Sign up to set email alerts
|

H. pylori cagL amino acid sequence polymorphism Y58E59 induces a corpus shift of gastric integrin α5β1 related with gastric carcinogenesis

Abstract: We tested whether cagL amino acid sequence polymorphisms of Helicobacter pylori correlated to clinico-histological outcomes and gastric α5β1 integrin expressions. One hundred forty five patients with H. pylori infection and 47 noninfected controls were enrolled to check gastric integrin α5β1 intensities topographically. The collected isolates were screened for cagL-genotype by polymerase chain reaction (PCR), and assessed for amino acid sequence polymorphisms using sequence translation. Our H. pylori isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
84
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(100 citation statements)
references
References 22 publications
10
84
5
1
Order By: Relevance
“…A study on 61 isolates from patients with digestive disease in Iran, showed that 96.7% were cagL positive. This report was concordant with the results from Taiwan, where the 98.6% of the patients were cagL positive, but no remarkable association was detected between the cagL genotype and clinical outcomes (P>0.05) (Kwok et al, 2007;Yeh et al, 2011;Wang et al, 2013;Yadegar et al, 2014). These results are consistent with our results in GC group but not in PU group, while the cagL genotype is remarkably and independently associated with the risk of PU in Iran (P=0.021), but no association was found with the risk of GC (P>0.05).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A study on 61 isolates from patients with digestive disease in Iran, showed that 96.7% were cagL positive. This report was concordant with the results from Taiwan, where the 98.6% of the patients were cagL positive, but no remarkable association was detected between the cagL genotype and clinical outcomes (P>0.05) (Kwok et al, 2007;Yeh et al, 2011;Wang et al, 2013;Yadegar et al, 2014). These results are consistent with our results in GC group but not in PU group, while the cagL genotype is remarkably and independently associated with the risk of PU in Iran (P=0.021), but no association was found with the risk of GC (P>0.05).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, it has been demonstrated that 86.6% of the H. pylori isolates from Indian patients were cagL positive. Other studies in Malaysia, Singapore, and Taiwan demonstrated that more than 85% of the isolates were cagL positive (Schmidt et al, 2010;Yeh et al, 2011). A study on 61 isolates from patients with digestive disease in Iran, showed that 96.7% were cagL positive.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The present study indicated 86.6 % of our isolates were cagL positive and all carried the RGD motif in their amino acid sequences. Studies from Malaysia, Singapore, and Taiwan reported [85 % prevalence of cagL in their H. pylori isolates, and the results are concordant with the current finding [15,16]. Moreover, the presence of RGD motif in all the current isolates suggests that the CagA translocation is mediated through an RGD-dependent pathway.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, it is rational to check whether the cagL amino acid sequence polymorphisms correlate with clinical disease. Previously, a study from Taiwan reported a higher rate of the amino acid sequence polymorphisms Y58 and E59 in GC patients (P \ 0.05) and concluded that cagL-Y58E59 isolates possibly exert stronger acid suppression during chronic infection [16]. On the other hand, the results of Saha et al [17] help in part to explain that CagL may dissociate ADAM17 of integrin a5b1 to contribute to hypochlorhydria during H. pylori infection.…”
Section: Discussionmentioning
confidence: 95%